Psychology and humanism in the democratic South African imagination - Seedat, Mohamed (South African journal of psychology, 2017)
Attentive to a psychology underlying South Africa’s democratic imaginations, I describe how Nelson Mandela’s intervention at a critical moment of conflict management, along with mechanisms such as at the Truth and Reconciliation Commission and the Moral Regeneration Movement, invoked and enacted a humanising ethos. Centred on the ideas of restraint, empathy, emotional proximity, witnessing, and fluid generative subjectivities, the humanising ethos was awakened to support the process of reconciliation, social justice, and the making of inclusive and socially just communities. Inspired by a decolonial attitude, and in part successfully enacted in support of the country’s liberal democratic ideals, the elaboration of this psychology has been limited by ongoing socio-economic disparities and a ruling psychology that naturalises extractive relations.